PERAN LEMBAGA SENI DAN BUDAYA MAHASISWA DALAM MEMBANGUN KARAKTER BERBASIS NILAI-NILAI BUDAYA - Siti Norhidayah; Reza Andri Astuti; Cahya Noormila; Yusika Amelia Putri; Muhammad Redha Anshari (CV. ADIBA AISHA AMIRA, 2025)
Culture-based character education is an urgent need in the midst of globalization that erodes the nation's identity. The role of culture in shaping character is often neglected in formal education, even though culture is the foundation of value formation and behavior. The Student Art and Culture Institute (LSBM) in this case has the potential to become a strategic space in instilling character values through cultural arts activities. This study aims to analyze the role of LSBM in shaping student character based on cultural values. The method used is a qualitative approach with a type of phenomenology, to explore the meaning of LSBM members' experiences. Data were obtained through observation and in-depth interviews with administrators and active members of LSBM IAIN Palangka Raya. Analysis was conducted through the stages of data condensation, data presentation, and conclusion drawing. The results showed that LSBM plays a strategic role in student character building through three main aspects: motivation, value internalization, and cultural roles. LSBM motivates students to actively develop their potential and strengthen their commitment to local and national cultural values. The process of internalizing values such as responsibility, cooperation, discipline, and tolerance occurs through direct involvement in arts and cultural activities. In addition, LSBM plays an important role as a space for culture-based character development that is participatory and contextual, so as to instill the nation's identity and noble values in the daily lives of students.